KEBERANIAN DALAM NOVEL TO KILL A MOCKINGBIRD KARYA HARPER LEE - Tiolemba, Melissa (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
The skripsi is entitled â€œKeberanian dalam Novel To Kill a Mockingbird by Harper Leeâ€. The objective of this research is to analyze the bravery as the main theme in the novel To Kill a Mockingbird. The data are collected by focusing on the character, plot and setting which describe about the main theme in the story. This research uses the theory of Stanton (1965) in analyzing the data. The writer uses descriptive method intrinsically. Intrinsic approach is to examine the elements within the novel itself; in this case, it is use to identify some characterâ€™s habits in connection with the theme by looking at other elements in the novel. The result of this research shows that Lee has the ability to express the bravery in every aspects of life in the Novel To Kill a Mockingbird based on the real life. the conclusion of the analysis about the main theme based on the character, plot and setting shows that The Finch who are the main characters in the novel To Kill a Mockingbird have a great bravery, never give up, and mature to see all the things. Lee was described the main theme with clearly explanation, it seen in the whole story To Kill a Mockingbird. Keywords: Theme, Bravery, and To Kill a Mockingbird